Low serum 25-hydroxyvitamin D is associated with increased risk of stress fracture during Royal Marine recruit training. Issue 1 (January 2016) - Davey, T.; Lanham-New, S.; Shaw, A.; Hale, B.; Cobley, R.; Berry, J.; Roch, M.; Allsopp, A.; Fallowfield, J.
Abstract Summary The aim of this study was to investigate vitamin D status and stress fracture risk during Royal Marine military training. Poor vitamin D status was associated with an increased risk of stress fracture. Vitamin D supplementation may help to reduce stress fracture risk in male military recruits with low vitamin D status. Introduction Stress fracture is a common overuse injury in military recruits, including Royal Marine (RM) training in the UK. RM training is recognised as one of the most arduous basic training programmes in the world. Associations have been reported between serum 25-hydroxyvitamin D (25(OH)D) and risk of stress fracture, but the threshold of 25(OH)D for this effect remains unclear. We aimed to determine if serum 25(OH)D concentrations were associated with stress fracture risk during RM training. Methods We prospectively followed 1082 RM recruits (males aged 16–32 years) through the 32-week RM training programme. Troops started training between September and July. Height, body weight and aerobic fitness were assessed at week 1. Venous blood samples were drawn at weeks 1, 15 and 32. Serum samples were analysed for 25(OH)D and parathyroid hormone (PTH). Results Seventy-eight recruits (7.2 %) suffered a total of 92 stress fractures. Recruits with a baseline serum 25(OH)D concentration below 50 nmol L−1 had a higher incidence of stress fracture than recruits with 25(OH)D concentration above this threshold (χ2 (1) = 3.564, p = 0.042; odds ratio 1.6 (95 % confidence interval (CI) 1.0–2.6)). Baseline serum 25(OH)D varied from 47.0 ± 23.7 nmol L−1 in February, to 97.3 ± 24.6 nmol L−1 in July (overall mean 69.2 ± 29.2 nmol L−1, n = 1016). There were weak inverse correlations between serum 25(OH)D and PTH concentrations at week 15 (r = −0.209, p < 0.001) and week 32 (r = −0.214, p < 0.001), but not at baseline. Conclusion Baseline serum 25(OH)D concentration below 50 nmol L−1 was associated with an increased risk of stress fracture. Further studies into the effects of vitamin D supplementation on stress fracture risk are certainly warranted.